Remaja pria 18 tahun dengan hipogonadotropik-hipogonadisme dan postur tubuh pendek: sebuah laporan kasus - Metanolia Sukmawati; Antonius Wahyudi; Judie Hartono; Tjahjo Djojo Tanojo (DiscoverSys Inc., 2019)
Background: Hypogonadotropic hypogonadism (HH) is congenital or acquired disease affects hypothalamus or pituitary, so the secretion of GnRH, FSH, LH, and testosterone are inadequate. Clinical manifestations both physical and psychological impair patient’s quality of life, so authors try to report this case.Case description: An 18 years old man complained about a small penis. Small penis cause patient had introvert personality and problems in social relations. On anthropometric status, body weight was below 3rd percentile, height was below 3rd percentile, and body mass index (BMI) was thin. The genital examination was 2nd-grade tanner, penis with 3 cm length and 3 cm circumference, minimal little pubic hair, and testicular volume <2 cc. Ultrasound examination showed no presence of testes in the right or left scrotum fossa, inguinal, and lumbar region. Chromosome analysis showed 46 XY, and hormones analysis found FSH, LH, and testosterone below the normal limit. The patient was given 2000 unit HCG injection and after that FSH, LH, and testosterone hormone increase compared before HCG injections.Conclusion: HH can impair physical and psychological patient’s quality of life through delays in sexual maturation and bone maturation. Strategies to recognize symptoms in early childhood and puberty induction on time can significantly improve the sexual and reproductive function of HH patients.